Corpos e vozes de matripotência: a palavra cantada por Anicide Toledo do Batuque de Umbigada de Capivari-SP na cosmopercepção do mulherismo africana - Faria, Lorena (2021)
The research work here present seeks a place of reexistence for the poetic work of woman black Anicide Toledo, singer and composer of the bantu cultural manifestation known as Batuque de Umbigada, Tambu or Caiumba, present in cities in the interior of São Paulo as Piracicaba, Barueri, Rio Claro, Tietê and Capivari. Born and created in the last city, master Anicide remodeled the batuqueira tradition because to be first woman to sing and compose 'modas' of batuque, at a time when the space occupied by the women in the manifestation was only the dance. From the Afrocentric Studies Perspective (ASANTE, 2009), the thesis seeks to analyze the context which manifestation Batuque de Umbigada is inserted - understood as 'Ancestral Celebratory Encounter' - goes through the understanding of the navel symbologies, walks towards the place occupied by men and women in the manifestation until focusing on the document-body (NASCIMENTO, 1989), voice and word sung by master Anicide Toledo. By highlighting the performance of the master, we seeks to understand how the matripotence is evidenced in umbigada's batuque, imbricated with ways of living bantu reterritorialized in brazilian soil by african people. With concepts of Pan-Africanist perceptions, we articulate the theoretical proposal of the Africana Womanism, a teoric of african-american teacher Clenora Hudson-Weems (2020) to challenge western genre conceptions. A collection of songs is also presented with approximately 70 ‘modas’ made by Anicide over more than half a century of experience in batuque, more a series of sheet music. The theoretical guiding bulge of the discussions finds its main south in the works of Oyèrónkẹ Oyěwùmí, Bunseki Fu-Kiau, Cheikh Anta Diop, Maria Beatriz Nascimento, Lélia Gonzalez, among other articulators and articulators, bringing African cosmogony, tracing decoloniality lines.